Investigating Mother Tongue Effect In The Acquisition Of English Prepositions By Indonesia-Speaking Learners - Budiharto, R. Agus; Rokhmawati, Dian (Journal of Educational Sciences, 2023)
The process of learning prepositions gets complicated most notably for learners of English as foreign language (EFL) because they encounter challenges in grasping the manifold meanings and dissimilar contextual applications. This study is aimed at identifying the sources of the difficulty that Indonesia learners of English undergo in learning preposition. To this end, a multiple-choice test was designed to gather data regarding the problems of acquiring and learning English prepositions by UNIRA students of English. The test comprised of fifteen questions. Each of the students was supposed to choice the best possible answer out of the choices from a list with the correct English preposition. In this study, method research design used is qualitative. The results suggest that the students meet considerable difficulties in using English prepositions. The students highly depend on their mother tongue, i.e. Indonesia language, which poses a source of command that enables the students in producing inappropriateness of preposition use.